Relationship Between Family Support With Compliance About The Treatment Of Hypertension Patients - Ni Made Sri Milandari; Made Rismawan; I GA Rai Rarayuni (Jurnal EduHealth, 2023)
Adherence to treatment in hypertensive patients is a major aspect in the healing process. In order for the healing process to be realized, it certainly requires cooperation between hypertension sufferers and their families. Family support is one of the factors that determine the level of patient compliance in carrying out the treatment process, the more obedient the patient is in undergoing treatment, the more complications from the disease will be avoided. This study aims to determine the relationship between family support and compliance with the treatment of hypertension patients. The design used in this study is descriptive correlative with a cross sectional approach. The sample used was 103 people taken by non-probability sampling technique with consecutive sampling approach. Retrieval of data using a questionnaire containing family support and the level of adherence to the theoryMorisky Medication Adherence Scale(MMAS-8). Furthermore, the data were analyzed using the Spearman Rho test. Results Most of the hypertensive patients received family support in a good category, namely 59 respondents (57.3%) and most of the adherence to treatment of hypertensive patients was still low, namely 45 respondents (43.7%). The results of bivariate analysis found that there was a significant relationship between family support and medication adherence in hypertension patients with p <0.001 with a value of r = 0.699. Family support has a role to increase patient or family member compliance, especially in hypertension, to undergo the treatment process.